2022
DOI: 10.14710/jkm.v10i1.31907
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan Dengan Ketidakpatuhan Kunjungan Kehamilan K1-K4 Pada Ibu Hamil Di BPM Bidan Mari Sentono, Pegadungan, Kalideres Tahun 2020

Abstract: One of the causes of Maternal Mortality Rate (MMR) is complications in pregnancy and childbirth. Complications of pregnancy and childbirth can be prevented by regular antenatal care (ANC) examinations. ANC is a visit by pregnant women with health workers to get pregnancy services in accordance with established standards. Of these 114 pregnant women patients, there were patients who were not compliant (having visits less than 4 times) as many as 89 (78%) patients while the data on the coverage of antenatal care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Another study showed that age, knowledge, attitudes, work, and family support are related factors influencing the frequency of antenatal care visits (Oktova, Halida, & Rusmat, 2023). Work is another aspect; according to (Fatmawati et al, 2022) research, moms who work will have less time to monitor their pregnancy, which indirectly limits their chance to gain more insight and knowledge because they work longer hours. While this is going on, stay-at-home women will have plenty of time to monitor their pregnancies and learn more about the advantages of ANC and ANC standards, directly increasing their level of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that age, knowledge, attitudes, work, and family support are related factors influencing the frequency of antenatal care visits (Oktova, Halida, & Rusmat, 2023). Work is another aspect; according to (Fatmawati et al, 2022) research, moms who work will have less time to monitor their pregnancy, which indirectly limits their chance to gain more insight and knowledge because they work longer hours. While this is going on, stay-at-home women will have plenty of time to monitor their pregnancies and learn more about the advantages of ANC and ANC standards, directly increasing their level of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…According to Fatmawati et al (2022) research, parity gives a mother's past pregnancies' experiences to draw on, which can indirectly affect her awareness of ANC visits. According to Qomar (2020) research, moms of first-time mothers feel that ANC is something new; thus, mothers are more motivated to adopt it since they are less worried about their pregnancies and hence make fewer visits.…”
Section: Discussionmentioning
confidence: 99%